Ethyl 3-(2-chloro-5,8-dimethoxyquinolin-3-yl)-2-cyanooxirane-2-carboxylate - Hayette Alliouche (Acta Crystallographica Section E, 2011)
The title molecule, C17H15ClN2O5, contains a quinolyl unit linked to a functionalized oxirane system with a 2,3-trans arrangement of the substituents (ester group versus quinolyl). The structure can be described as being built up from zigzag layers parallel to (1overline{1}0). The heterocyclic ring of the quinolyl unit forms a dihedral angle of 60.05 (1)° with the oxirane plane. The crystal packing is stabilized by intermolecular C—H...O and C—H...N hydrogen bonding, resulting in the formation of an infinite three-dimensional network and reinforcing the cohesion between the layers.